Effect of sodium alginate coating containing clove essential oil on pH, cooking loss, colour and sensory attributes of refrigerated rabbit meat - Rusman, Aifa Hazurin; Kumar, Pavan; Hayat, Muhammad Nizam; Abdul, Mustapha; Adamu, Garba; Ismail-Fitry, Mohammed Rashedi; Sazili, Awis Qurni (ACS Publisher, 2024)
The present study was undertaken to assess the effect of coating added with clove essential oil on meat quality attributes of rabbit meat. The fresh rabbit meat was categorized into 4 treatments viz., control (C)- without coating, T1- coated with alginate coating, T2- coated with alginate coating added with 0.2% clove essential oil, and T3- coated with alginate coating added with 0.5% clove essential oil. The samples were aerobically packaged in low-density polyethylene (LDPE) packs and stored under refrigeration (4±1ºC) for 7 days. The samples were assessed on day 0 (before keeping the samples in refrigeration), days 1, 3, 5, and 7 for pH, cooking loss, colour profile, and sensory attributes. The alginate coating was observed to significantly (p<0.05) increase the pH value of the raw rabbit meat samples. Throughout the storage, the raw C sample recorded significantly (p<0.05) lower pH values than those of the raw-treated samples. The coating of the rabbit meat sample did not have any significant effect on the cooking loss except on day 0 of storage. With the advancement of the storage period, the treated samples retained a better colour and sensory attribute. The T3 sample had the highest sensory scores throughout the storage period. Thus, alginate coating added with 0.5% clove essential oil could be used to improve the quality of rabbit meat.